An In-depth Analysis of the Relation of Health and Poverty in Europe - Apostu, Simona Andreea; Dimian, Gina Cristina; Vasilescu, Maria Denisa (Panoeconomicus, 2024)
Our article aims to present an in-depth analysis of the correlation between health status and poverty in European countries. Our research is grounded on two types of data: a survey of the perceptions of the European citizens related to their own physical and mental health conducted in 2017 in European Union countries and the United Kingdom on a sample of 28,000 respondents and macroeconomic data retrieved from Eurostat Database, showing the incidence of poverty and working poor in Europe during the 2017–2019 time span. Multiple logistic regression has revealed that self-rated health status is influenced by the sociodemographic characteristics of the respondents, whereas TwoStep Cluster analysis and Mann–Whitney U test proved that health is an important driver of the differences between countries in terms of poverty and working poor. The originality of our research stems from both the integrated approach, the analysis being made at individual, group, and country levels, and by the results that bring new evidence about population health status as a determinant of quality of life and national competitiveness. Keywords: Physical health, Mental health, Poverty, Working poor, Logistic regression, Cluster analysis. JEL: C38, I15, P46.